1989
DOI: 10.1152/ajpheart.1989.257.5.h1736
|View full text |Cite
|
Sign up to set email alerts
|

Postocclusive cerebral hyperemia is markedly attenuated by chronic trigeminal ganglionectomy

Abstract: Marked hyperemia may develop in brain following temporary cessation of blood flow and is associated with the morbidity following cardiac arrest, stroke, and head injury. Regional cerebral blood flow was measured using radiolabeled microspheres and compared in 10 symmetrical regions after chronic unilateral trigeminal ganglionectomy (n = 8), trigeminal rhizotomy (n = 4), or sham operation (n = 4) following 10 min of combined brachiocephalic-left subclavian occlusion and hypotension (mean arterial blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…For exam ple, the hyperemic response to acute severe hypertension beyond the limits of autoregu lation, or to acute generalized seizures, is reduced following trigeminal ganglionecto my, but not following trigeminal rhizotomy [6,7]. Because section of the nerve root pre vents central transmission but does not cause wallerian degeneration of peripheral axons, the increases in CBF are mediated by axon-reflex-like mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For exam ple, the hyperemic response to acute severe hypertension beyond the limits of autoregu lation, or to acute generalized seizures, is reduced following trigeminal ganglionecto my, but not following trigeminal rhizotomy [6,7]. Because section of the nerve root pre vents central transmission but does not cause wallerian degeneration of peripheral axons, the increases in CBF are mediated by axon-reflex-like mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…of either sex and weighing 2.2-5.2 kg, were used for all experiments. Chronic left trigeminal ganglionectomy was per formed in 8 animals [5][6][7],…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Moskowitz et al 19 suggest that nerves, albeit nonsympathetic nerves, are capable of modifying postischemic hyperemia. We found that epinephrine infusion increased plasma levels approximately 10-fold over that in the control group with aortic balloon inflation, but that CBF was similar over an equivalent range of cerebral perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%